Redox Imbalance in T Cell-Mediated Skin Diseases - Saveria Pastore; Liudmila Korkina (Mediators of Inflammation)
The skin is permanently exposed to physical, chemical, and biological aggression by the environment. In addition, acute and chronic inflammatory events taking place in the skin are accompanied by abnormal release of pro-oxidative mediators. In this paper, we will briefly overview the homeostatic systems active in the skin to maintain the redox balance and also to counteract abnormal oxidative stress. We will concentrate on the evidence that a local and/or systemic redox dysregulation accompanies the chronic inflammatory disorder events associated to psoriasis, contact dermatitis, and atopic dermatitis. We will also discuss the fact that several well-established treatments for the therapy of chronic inflammatory skin disorders are based on the application of strong physical or chemical oxidants onto the skin, indicating that, in selected conditions, a further increase of the oxidative imbalance may lead to a beneficial outcome.